Satisfaction of Nigerian Stroke Survivors with Outpatient Physiotherapy Care (2017)
Objective: To investigate the satisfaction of stroke survivors with outpatient physiotherapy care. Methods: Sixty stroke survivors were surveyed using the European Physiotherapy Treatment Outpatient Satisfaction Survey (EPTOPS). Focus group discussion (FGD) was also conducted with four stroke survivors from the same sample. Data were analyzed using the Kruskal Wallis test and Spearman’s correlation coefficients at p = 0.05. FGD was transcribed and thematically analyzed. Results: Nearly all the participants (98.3%) indicated one of good, very good, and excellent improvement in their clinical conditions with physiotherapy. Majority expressed satisfaction with their physiotherapy care, the modal response being very good (59.3%). Patients’ satisfaction and socio-demographics were not significantly correlated (p > 0.05). Overarching themes from FGD were physiotherapy in stroke rehabilitation, satisfaction with physiotherapy care, cost, and lack of continuity of care as sources of dissatisfaction. Physiotherapists’ demeanor was a facilitator of satisfaction. Conclusion: The stroke survivors were generally satisfied with outpatient physiotherapy care. However, lack of continuity and cost of care were sources of dissatisfaction among patients. Delivery of physiotherapy to stroke survivors in Nigeria should be structured to allow for continuity of care as this may enhance satisfaction. Implementation of inexpensive rehabilitation strategies may help reduce cost of physiotherapy.